Effectiveness of video-assisted planned teaching intervention on knowledge regarding weaning among mothers - Archana Yadav; Nitasha Rai; Sunita Devi; Devendra Singh; Prabhawati Singh; Priyanshi Dixit (Journal of Family Medicine and Primary Care)
Aim: It is an integral part of the transitional phase in a child’s life as weaning for satisfactory growth and development. Effective weaning in the child requires proper knowledge and good technique skills in the mother. The present study aimed to evaluate the effectiveness of education video intervention in increasing weaning knowledge among rural mothers. Method: A quasi-experimental one-group pre-test and post-test design were adopted to study conveniently selected 60 mothers of 0-4-year-old infants in a designated rural area of Kanpur district. Result: In the pre-test, the majority of mothers of infants i.e., 70.0% had average knowledge and only 26.66% had good knowledge regarding Weaning with a mean knowledge score was 17.33 ± 4.95. In the post-test, the majority of mothers of infants i.e., 83.33% had excellent knowledge and none of the participants had poor knowledge. After implementing the video Teaching Intervention programme knowledge score increased to 33.0 ± 4.76 and was found to be significant (P < 0.001). Conclusion: The study suggests that video teaching programmes regarding weaning have a great impact on knowledge regarding weaning among mothers of infants aged 0-4 years Some socio-demographic variables like parity of mothers and educational background influence the post-test knowledge score significantly.